SUPPLIER ASSESSMENT FOR SUPPLY CHAIN PERFORMANCE AND EFFECTIVE FOOD SAFETY IMPLEMENTATION: A FRAMEWORK - N. Nurhayati; Muhammad Zulfikar (LPSDI Bina Patria, 2023)
Purchasing raw foods materials that are used to make our product must be carefully controlled. Selecting and evaluating the right food supplier today has become much more critical and complex. Involving process of selecting the right supplier can help many food industries and restaurants meet or exceed regulatory standards, drive customer demand, and build a strong brand reputation of quality products. Quality and safety for ingredients, products, and packaging are mandatory requirements for every food business, so choosing a good supplier is a critical business decision. Consequently, the supply chain team has needed to identify choosing the right supplier, as well as several best practices in the food industry or restaurant. This paper’s objective is to frame working best practices on food supplier selection and, assessment as part of supply chain sustainability and food safety implementation. Establishing close working relationships with foods supplier and providing them with high standards also providing feedback on their performance would be part of effective supplier programs in food safety assessment. Some criteria that should be provided by our food supplier were considered as approved suppliers such as purchasing specification, quality system compliance, Regulatory compliance, and certificate of analysis. The study found that trust and communication are key elements in establishing strong working relationships with foods supplier. Working relationships with food suppliers have become a competitive advantage for Food Industries and Restaurants looking for long-term economic success. Trusted food suppliers were described as communicating effectively and demonstrating a willingness to work collaboratively. Foods suppliers who communicate directly and clearly are more effective in implementing Food Safety assessments.